TMAZ microcracking in inertia friction welding of PM RR1000 superalloy: concomitant effect of constitutional liquating particles (2010)
The effect of constitution liquidation of strengthening particles in PM RR1000 superalloy in response to inertia friction welding process was investigated. The thermomechanical affected zone(TMAZ) microstructures were simulated using Gleeble® thermomechanical simulation system. The microstructural examination of the simulated TMAZs and those from the actual welded specimens showed the occurance of extensive grain boundary liquidation of the main strengthening phase ƴ and MC type carbide and consequently attendant microcracking in the TMAZ of the alloy. The existence of these particles in the temperature range well above thier solvus temperatures orchestrated the eutectic type reaction to their constitutional liquidation and subsequent cracking of the weldment.